Perceived Quality Of Building Permit Services And Local User Charges In Malinau: Persepsi Kualitas Pelayanan Izin Mendirikan Bangunan Dan Retribusi Daerah Di Kabupaten Malinau - Aswin Anasis Palete; Riswanda Riswanda; Agus Susanto (Academia Open, 2026)
General Background: Local governments rely on building permit services as part of public administration and local own-source revenue management. Specific Background: In Malinau Regency, the One-Stop Investment and Integrated Services Office administers Building Permit (IMB) services that remain administratively relevant during the transition toward new licensing arrangements. Knowledge Gap: Previous studies largely assess service quality or revenue performance separately, with limited descriptive integration of user perceptions and IMB user charge trends in frontier regions. Aims: This study aims to describe public perceptions of IMB service quality and examine its descriptive linkage with IMB user charge performance as a component of local revenue. Results: Using a SERVQUAL-based survey of 41 IMB service users and administrative data from 2017–2023, findings indicate that perceived IMB service quality is categorized as good, with an overall index score of 78.96%, while several indicators related to timeliness, information clarity, and procedural consistency remain less optimal. Administrative records show fluctuating IMB user charge realization across years. Novelty: This study offers a contextual descriptive profile combining service quality perceptions and revenue trends in a frontier local government during the final implementation phase of IMB. Implications: The findings provide an empirical basis for service improvement strategies in permit administration and support more accountable local revenue governance without asserting causal relationships. Highlights • IMB service quality in Malinau is perceived as good across SERVQUAL dimensions• Service indicators related to timeliness and information remain less optimal• IMB user charge realization shows notable annual fluctuations Keywords Service Quality; SERVQUAL; Building Permit; Local User Charges; Local Revenue